Feasibility of implementing public-private mix approach for tuberculosis case management in Pokhara Metropolitan City of western Nepal: a qualitative study - Baral, Sushila; Yadav, Rajesh Kumar; Yadav, Dipendra Kumar; Marahatta, Sujan Babu; Baral, Yadunath; Khadka, Khim Bahadur; Thakur, Sanjay Kumar; Paudel, Srijana; Sharma, Prabin; Pandey, Sony; Shrestha, Kusum; Shah, Naveen Prakash; et al. (Frontiers in Public Health, 2023)
Background Public Private Mix (PPM) approach is a strategic initiative with the objective of engaging all private and public health care providers in the fight against tuberculosis, using international health care standards. For tuberculosis control in Nepal, PPM approach could be the milestone. This study aimed to explore the barriers to public-private mix approach in the management of tuberculosis case in Nepal. Methods: We conducted key informant interviews with twenty participants, fourteen of whom were from private clinics, polyclinics, and hospitals where the PPM approach was used, two from government hospitals, and four from policymakers. All data was recorded on audio, transcribed, and translated into English. The transcripts of the interviews were manually organized, and themes were generated for TB case detection, patients-related, and health-system-related barriers. Results: Twenty people were interviewed in total. The average age of respondents was 32.85 years, with a range of 23 to 57 years. Several barriers were discovered and classified into three themes: 1) Obstacles to detecting tuberculosis cases 2) Patient-related impediments 3) Obstacles in the health-care system. Staff turnover, low private sector participation in workshops, a lack of trainings, poor recording and reporting, insufficient joint monitoring and supervision, financial benefit, coordination and collaboration, and TB-related policies and strategies were identified as barriers to PPM implementation for TB case findings. Conclusion: Government stakeholders must work together with the private sector to perform joint monitoring and supervision. Private practitioners should receive training and orientation, and presumptive TB patients should be given adequate time and counseling, as well as motivation to visit a government health facility.